Genome-Wide Identification of Two-Component System Genes in Cucurbitaceae Crops and Expression Profiling Analyses in Cucumber - He, Yanjun; Liu, Xue; Zou, Tao; Pan, Changtian; Qin, Li; Chen, Lifei; Lu, Gang (Frontiers in Plant Science, 2016)
Cucumber and watermelon, which belong to Cucurbitaceae family, are economically important cultivated crops worldwide. However, these crops are vulnerable to various adverse environments. Two-component system (TCS), consisting of histidine kinases (HKs), phosphotransfers (HPs), and response regulator proteins (RRs), plays important roles in various plant developmental processes and signalling transduction in responses to a wide range of biotic and abiotic stresses. No systematic investigation has been conducted on TCS genes in Cucurbitaceae species. Based on the completion of the cucumber and watermelon genome draft, we identified 46 and 49 TCS genes in cucumber and watermelon, respectively. The cucumber TCS members included 18 HK(L)s, 7 HPs, and 21 RRs, whereas the watermelon TCS system consisted of 19 HK(L)s, 6 HPs, and 24 RRs. The sequences and domains of TCS members from these two species were highly conserved. Gene duplication events occurred rarely, which might have resulted from the absence of recent whole-genome duplication event in these two Cucurbitaceae crops. Numerous stress- and hormone-responsive cis-elements were detected in the putative promoter regions of the cucumber TCS genes. Meanwhile, quantitative real-time PCR indicated that most of the TCS genes in cucumber were specifically or preferentially expressed in certain tissues or organs, especially in the early developing fruit. Some TCS genes exhibited diverse patterns of gene expression in response to abiotic stresses as well as exogenous trans-zeatin (ZT) and abscisic acid (ABA) treatment, suggesting that TCS genes might play significant roles in responses to various abiotic stresses and hormones in Cucurbitaceae crops.